2007
DOI: 10.1021/jp0762774
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Engineering in Two Dimensions:  An Approach to Molecular Nanopatterning

Abstract: We describe a surprising cooperative adsorption process observed by scanning tunneling microscopy (STM) at the liquid-solid interface. The process involves the association of a threefold hydrogen-bonding unit, trimesic acid (TMA), with straight-chain aliphatic alcohols of varying length (from C 7 to C 30 ), which coadsorb on highly oriented pyrolytic graphite (HOPG) to form linear patterns. In certain cases, the known TMA "flower pattern" can coexist temporarily with the linear TMA-alcohol patterns, but it eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
173
1
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 128 publications
(188 citation statements)
references
References 68 publications
10
173
1
4
Order By: Relevance
“…The most stable of the two quadruple tapes is reported in Fig. 15b: it is based on the doubling of thermodynamically stable TMA dimers [10], in an eclipsed manner. In the less stable quadruple-TMA (Fig.…”
Section: Tma and Other Benzoic Acidsmentioning
confidence: 99%
See 3 more Smart Citations
“…The most stable of the two quadruple tapes is reported in Fig. 15b: it is based on the doubling of thermodynamically stable TMA dimers [10], in an eclipsed manner. In the less stable quadruple-TMA (Fig.…”
Section: Tma and Other Benzoic Acidsmentioning
confidence: 99%
“…Recently, Nath and co-workers showed that the threefold symmetry patterns (flower or chicken-wire), which TMA forms on threefold symmetry substrates (HOPG in this case), can be broken by introducing an alcohol to the solution [10,62]. For example, when using 1-undecanol, the well-known flower structure is found to be surrounded by a linear pattern, which is a novel TMA polymorph.…”
Section: Tma and Other Benzoic Acidsmentioning
confidence: 99%
See 2 more Smart Citations
“…[8,9] The investigation of molecular organization at the SSI is largely conducted via scanning tunnelling microscopy (STM), which can be used to directly visualize molecular kinetics and geometries in situ. [10][11][12][13][14] The development of this technique has provided unprecedented access to the details of surface molecular self-assembly. [15,16] The Gibbs free energy for molecular systems at the SSI comprises an enthalpic contribution dominated by the interaction energies of the adsorbed species (intermolecular and molecule-substrate) and an entropic component primarily associated with the molecules in solution.…”
mentioning
confidence: 99%